2020
DOI: 10.2141/jpsa.0190014
|View full text |Cite
|
Sign up to set email alerts
|

Meat Quality and Cooking Characteristics in Broilers Influenced by Winter Transportation Distance and Crate Density

Abstract: A study was conducted to determine the effect of transportation distance and crating density on meat quality traits during winter. ROSS-308 broilers aged 35 days were divided into 10 treatment groups based on three transportation distances (80, 160, and 240 km) with three crating densities (10, 12, and 15 birds per crate) along with birds slaughtered on farm without crating as a control group. Each treatment was replicated 10 times and placed at various locations in the truck. The birds were transported in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…[13] carried out investigations involving various crating densities (10, 12, and 15 birds per crate) during the summer, but they found no statistically significant difference in pH associated with crating density. Likewise, [19] reported that no significant pH differences were…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] carried out investigations involving various crating densities (10, 12, and 15 birds per crate) during the summer, but they found no statistically significant difference in pH associated with crating density. Likewise, [19] reported that no significant pH differences were…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Previous studies have reported that broilers transported at higher crating densities exhibited severe body weight loss and a decline in both physical appearance and functional properties during the summer season (27.2-33.6 ℃, 52.7-62.9%). In contrast, low crating density adversely impacted meat quality by leading to increased weight loss and stress in winter (3.6-9.5 ℃, 63.3-78.8%) [18][19][20]. Another study by [21] examined the impact of various crating densities and seasonal variations [low air temperature (-9 ℃, 60%), high air temperature (27 ℃, 80%)] on preslaughter losses, meat quality, and physiological characteristics in broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies should be conducted with the purpose of establishing standards of broiler welfare related to corticosterone levels, as they already exist for other parameters, such as for standardized DOA by Grandin [10]. Poultry processing plant managers must realise that animal welfare problems during the transportation of broilers not only cause direct losses such as DOA and injuries [52,53], but also regarding the overall loss of meat quality due to the deterioration of the physical appearance and its functional characteristics [54][55][56][57][58][59][60]. In addition, it could also contribute to raising the levels of pathogens in chicken carcasses, such as Campylobacter spp.…”
Section: Apdv000685 8(2)2021mentioning
confidence: 99%